Role of Religious Attendance and Identity Conflict in Psychological Well-being - Hamblin, Rebecca (Journal of religion and health, 2013)
A sample of individuals who identified as gay or lesbian were administered measures of church attendance, their religious organization's view of homosexuality, perceived conflict between religious faith identity and sexual orientation identity, social support, depression, and generalized anxiety. Among participants who rated their church as rejecting of homosexuality, greater frequency of attendance was related to a higher incidence of GAD symptoms, but not depression. No correlation was found for those attending accepting faith communities. Those who attend rejecting faith communities attended services less often, experienced greater identity conflict, and reported significantly less social support than those of the Accepted group. Regression analyses indicated that identity conflict and social support did not fully account for the relationship between attendance and GAD symptoms. Overall, findings from the current study support previous suggestions that participation in conservative or rejecting religious communities may adversely affect the emotional well-being of GL individuals.